2019
DOI: 10.1002/cite.201900109
|View full text |Cite
|
Sign up to set email alerts
|

Models for the Numerical Simulation of Bubble Columns: A Review

Abstract: This work reviews the state‐of‐the‐art models for the simulation of bubble columns and focuses on methods coupled with computational fluid dynamics (CFD) where the potential and deficits of the models are evaluated. Particular attention is paid to different approaches in multiphase fluid dynamics including the population balance to determine bubble size distributions and the modeling of turbulence where the authors refer to numerous published examples. Additional models for reactive systems are presented as we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 142 publications
1
22
0
1
Order By: Relevance
“…Thus, solid particle effects on the spatial gas fraction distributions can be shown with ERT and may also serve for comparison with 3D simulations, e.g., computational fluid dynamic (CFD) simulations. Furthermore, such a data base is still necessary with regard to model development and testing for disperse gas-liquid-solid flows, especially including breakage and coalescence phenomena [26].…”
Section: Flow Regime Visualizationsmentioning
confidence: 99%
“…Thus, solid particle effects on the spatial gas fraction distributions can be shown with ERT and may also serve for comparison with 3D simulations, e.g., computational fluid dynamic (CFD) simulations. Furthermore, such a data base is still necessary with regard to model development and testing for disperse gas-liquid-solid flows, especially including breakage and coalescence phenomena [26].…”
Section: Flow Regime Visualizationsmentioning
confidence: 99%
“…In this case, random perturbations of the abscissas may be employed to overcome this problem [89]. Furthermore, it has been shown that the classical DQMoM formulation generally does not conserve moments of order higher than one when applied to systems with spatial gradients in the disperse phase, e.g., gas-solid fluidized beds [105], exhaust particle formation [106], or bubbly flows [107,108]. For that case, Buffo and coworkers [109] presented a fully conservative formulation.…”
Section: Direct Quadrature Methods Of Moments (Dqmom)mentioning
confidence: 99%
“…For disperse systems, the Euler-Lagrange and Euler-Euler approach are mainly used, whereby the latter is state of the art [107,138]. An overview of the state of the art of multiphase modeling can be found in [139].…”
Section: Two-fluid Modelmentioning
confidence: 99%
“…The breakup model of Laakkonen et al [237] was developed for stirred reactors and is very common in the literature. Other frequently used approaches are the models of Prince & Blanch [238], Luo & Svendsen [239] and Lehr et al [100,139].…”
Section: Population Balance Modelmentioning
confidence: 99%